Clinical validation of nuclear factor kappa B expression in invasive breast cancer. Issue 1 (January 2018) - Agrawal, Anil Kumar; Pielka, Ewa; Lipinski, Artur; Jelen, Michal; Kielan, Wojciech; Agrawal, Siddarth
Breast cancer is the most commonly diagnosed cancer in Polish women. The expression of transcription nuclear factor kappa B, a key inducer of inflammatory response promoting carcinogenesis and cancer progression in breast cancer, is not well-established. We assessed the nuclear factor kappa B expression in a total of 119 invasive breast carcinomas and 25 healthy control samples and correlated this expression pattern with several clinical and pathologic parameters including histologic type and grade, tumor size, lymph node status, estrogen receptor status, and progesterone receptor status. The data used for the analysis were derived from medical records. An immunohistochemical analysis of nuclear factor kappa B, estrogen receptor, and progesterone receptor was carried out and evaluation of stainings was performed. The expression of nuclear factor kappa B was significantly higher than that in the corresponding healthy control samples. No statistical difference was demonstrated in nuclear factor kappa B expression in relation to age, menopausal status, lymph node status, tumor size and location, grade and histologic type of tumor, and hormonal status (estrogen receptor and progesterone receptor). Nuclear factor kappa B is significantly overexpressed in invasive breast cancer tissues. Although nuclear factor kappa B status does not correlate with clinicopathological findings, it might provide important additional information on prognosis and become a promising object for targeted therapy.